The effects of acute phosphate supplementation in subjects of different aerobic fitness levels - Galloway, S. D.; Tremblay, M. S.; Sexsmith, J. R.; Roberts, C. J. (European Journal of Applied Physiology, 1996)
Six trained cyclists (high-fitness group) and six untrained individuals (low-fitness group), performed a 20-min cycle ergometer exercise test at 70% of maximum oxygen consumption (VO2max) followed by a 30-min rest period and then an incremental ride to exhaustion on two occasions, 1 week apart. Ninety minutes prior to exercise subjects consumed a drink containing either 22.2 g dibasic calcium phosphate (DCP; treatment) or calcium carbonate (placebo). Blood was drawn prior to drink ingestion, during submaximal exercise, during recovery and at exhaustion for determination of blood 2,3-DPG, blood ATP, plasma lactate, plasma phosphate, haemoglobin and haematocrit. Throughout exercise, cardiorespiratory variables [oxygen uptake (VO2), minute ventilation, (VE), respiratory exchange ratio, heart rate and oxygen pulse] were monitored, and ratings of perceived exertion obtained. Although there was a trend for the low-fitness group to have a higher plasma phosphate concentration prior to treatment ingestion, no treatment effects on plasma phosphate were noted at any sample time in either group. 2,3-DPG, VO2, oxygen pulse, VE, time to exhaustion and VO2max were significantly higher in the high-fitness group; however, no differences in these variables were observed as a result of phosphate ingestion. Plasma lactate was significantly lower in the high-fitness group during the submaximal exercise and the recovery period, but again phosphate ingestion had no effect. These results suggest that acute DCP supplementation is not effective as an ergogenic aid and that aerobic fitness level does not affect the response to phosphate supplementation.